(3QSGdI aj JMbjb GdYdes - (3CMeO Hf EHQGgje GdMSjfj GdefUhQjs
(3ChdgG (B:s
(3GdMeO ddg (B... (3Ef LeGYI ef GdCMHGH hNGdU GdCUMGH GdPjf ejRhG GdeGA aj GdTQGH bO WdHhG ef GdabjQ GdMbjQ Cf CcJH cdeGJ aj cjajI GdSdhc Edi Gddg JYGdi hWdH bQHg hQVGg (B..s
(3BNQgG (B:s
.. (3Gf JdGMX GdCMO GdMb GdeYHhO SHMGfg hJYGdi hJJhLg Edjg HPGJc hMbjbJc eG MjG faSc hfGSjG PGJc aJSJZQb aj cHQ GdJhMjO hJSjM aj dLI GdJZQjO (B..(3gfG GfbWY GdcdGe (B.s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds